Early mechanical properties and strength calculation method of slag-based alkali activated concrete - Yuhua Wang; Congrong Tang; Mengjun Wang; Yong Yu; Shuai Chen (AIP Advances, 2024)
The use of slag-based alkali-activated concrete (AAC) could effectively address the issues of resource extraction and carbon emissions caused by traditional Portland cement. In this study, the effects of the fly ash content, water–binder ratio, and alkali activation modulus on the early mechanical properties of AAC were investigated. A total of 105 cube specimens (35 sets) were designed and subjected to compressive strength tests, scanning electron microscope tests, and x-ray diffraction composition analysis. The results indicated that excellent early strength was observed in AAC, with a compressive strength reaching ∼90% of the 28th day strength before 14 days. An increase in the fly ash content and a decrease in the water–binder ratio significantly improved the compressive strength within the same age period. The impact of a lower alkaline activation modulus on strength was found to be insignificant. Based on the experimental results, a calculation method and a constitutive model for early strength were proposed, and the theoretical values exhibited a high level of agreement with the measured values.